2018
DOI: 10.1098/rsbl.2018.0065
|View full text |Cite
|
Sign up to set email alerts
|

The pitch of babies’ cries predicts their voice pitch at age 5

Abstract: Voice pitch (fundamental frequency, ) is a key dimension of our voice that varies between sexes after puberty, and also among individuals of the same sex both before and after puberty. While a recent longitudinal study indicates that inter-individual differences in voice pitch remain stable in men during adulthood and may even be determined before puberty (Fouquet 2016 , 160395. (doi:10.1098/rsos.160395)), whether these differences emerge in infancy remains unknown. Here, using a longitudinal study design, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…These results suggest that, in addition to valance-specificity, individual differences in F0 are also more strongly preserved within the broader category of emotional (compared to neutral) sounds. These results complement two longitudinal studies that recently showed that the F0 of babies' cries predicts the F0 of their speech later in childhood [28], and that individual differences in F0 stabilize after puberty [27], suggesting that voice pitch is determined early in life and remains fairly stable throughout adulthood [27,28]. Those findings, together with the results of the present study and other recent work showing that individuals can generally be recognized when producing emotional speech [21], laughter [22], cries [23] and screams ( [24], cf.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggest that, in addition to valance-specificity, individual differences in F0 are also more strongly preserved within the broader category of emotional (compared to neutral) sounds. These results complement two longitudinal studies that recently showed that the F0 of babies' cries predicts the F0 of their speech later in childhood [28], and that individual differences in F0 stabilize after puberty [27], suggesting that voice pitch is determined early in life and remains fairly stable throughout adulthood [27,28]. Those findings, together with the results of the present study and other recent work showing that individuals can generally be recognized when producing emotional speech [21], laughter [22], cries [23] and screams ( [24], cf.…”
Section: Discussionsupporting
confidence: 87%
“…[25]) and non-human primates [26] (with the caveat that speaker recognition is substantially reduced from these vocalizations compared to modal speech among human listeners [21,22,25]). Finally, longitudinal studies have recently revealed that individual differences in F0 remain relatively stable across the lifespan, from infancy to childhood and throughout adulthood [27,28]. Taken together, this body of literature suggests that F0 may represent a reliable and surprisingly stable individual marker despite its extreme dynamicity at the within-vocalizer level (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results also support the validity of longitudinal analyses of mean f o measured from the same individuals at different time points, often from different speech utterances (e.g. [19,20,26]). It is and male (n = 71, blue squares) vocalizers (Pearson's r, two-tailed, alpha 0.05), where only age predicted f o , and only in women (***p < 0.01).…”
Section: Discussionsupporting
confidence: 73%
“…It is the vast inter-individual, within-sex differences in voice pitch that have been repeatedly linked to individual differences in various biosocial traits. Recently, studies have further revealed that between-individual differences in mean f o emerge early in life and remain remarkably stable thereafter, as the cries of 4-month-old infants predict their speech f o in childhood [19], and pre-pubertal f o predicts post-pubertal f o in males across the lifespan [20].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, or in addition, sociocultural norms related to speaking styles and vocal pitch (e.g., Loveday, 1981;Pemberton, McCormack, & Russell, 1998;Starr, 2015) may have contributed to the presence or absence of correlations between chronological age and F0 in the present cross-sectional data. It may be noted that, according to recent longitudinal data, interindividual differences in vocal pitch appear stable after puberty and throughout adulthood in men (Fouquet, Pisanski, Mathevon, & Reby, 2016) and in young pre-pubertal children (Levrero, Mathevon, Pisanski, Gustafsson, & Reby, 2018).…”
Section: The Role Of Speaker Age and Sex For Voice Ratingsmentioning
confidence: 95%